Congestion and Air Transport: a challenging phenomenon - Roosens, Paul (European Journal of Transport and Infrastructure Research, 2008)
This paper deals with the problem of congestion in air transport. The focus is on the congested related delays at airports and en route. One of the solutions in the longer run is additional investment in new infrastructure, but in this article the major attention goes to the short run operational techniques to optimize the use of existing capacity. The pricing mechanism and slot allocation do not constitute a basic part of this article, as many academic publications already exist on these issues. During the years a lot of experience and successful solutions have been adopted in the US by the FAA and in Europe by the European Union and Eurocontrol. Whatever the solutions, constantly new challenges are looming beyond the horizon. Especially the relationship between noise related concerns and congestion is actually becoming a major problem.